2020
DOI: 10.1007/s00603-020-02228-7
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Shaft Resistance of Driven Piles Penetrating Weak Rock

Abstract: In this paper, an empirical relationship between the Unconfined Compressive Strength (UCS) of intact rock and the unit shaft resistance of piles penetrating rock is investigated. A growing number of civil engineering projects are utilizing steel piles driven into rock where a significant portion of the pile capacity is derived from the shaft resistance. Despite the growing number of projects utilizing the technology, little to no guidance is offered in the literature as to how the shaft resistance is to be cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Choo et al [52] carried out centrifuge testing to investigate the lateral behavior of a 6 m diameter monopile with an embedment of 31 m (at prototype scale), used as a foundation for an offshore wind turbine. Different soil and rock characteristics were considered in the tests; two tests simulated a monopile installed in a dense sand and socketed into rock [53], while another two tests simulated monopiles installed in homogeneous sand with relative density of 85%. While combined loading was not explicitly considered, it is suggested that the self-weight of the monopile and extension rod acting as an additional vertical load may be one reason for the observed lateral displacements being larger than expected, when compared against those predicted by design codes [54].…”
Section: N-g Centrifuge Model Pile Testsmentioning
confidence: 99%
“…Choo et al [52] carried out centrifuge testing to investigate the lateral behavior of a 6 m diameter monopile with an embedment of 31 m (at prototype scale), used as a foundation for an offshore wind turbine. Different soil and rock characteristics were considered in the tests; two tests simulated a monopile installed in a dense sand and socketed into rock [53], while another two tests simulated monopiles installed in homogeneous sand with relative density of 85%. While combined loading was not explicitly considered, it is suggested that the self-weight of the monopile and extension rod acting as an additional vertical load may be one reason for the observed lateral displacements being larger than expected, when compared against those predicted by design codes [54].…”
Section: N-g Centrifuge Model Pile Testsmentioning
confidence: 99%
“…Liu et al conducted a vertical static load test and an internal force test on a rock-socketed pile and summarized the load-settlement curve of a rock-socketed pile, as well as the variation law of axial force and lateral resistance along the depth [6]. Barrett and Prendergast summarized the empirical relationship between the compressive strength of the surrounding rock in the rock-socketed section and the bearing capacity of a single pile based on a large number of field load tests of rocksocketed piles [7].…”
Section: Introductionmentioning
confidence: 99%